OGG1 competitive inhibitors show important off-target effects by directly inhibiting efflux pumps and disturbing mitotic progression - Tanushi, Xhaferr; Pinna, Guillaume; Vandamme, Marie; Siberchicot, Capucine; D’Augustin, Ostiane; Di Guilmi, Anne-Marie; Radicella, J. Pablo; Castaing, Bertrand; Smith, Rebecca; Huet, Sebastien; Leteurtre, François; Campalans, Anna (Frontiers in Cell and Developmental Biology, 2023)
One of the most abundant DNA lesions induced by Reactive oxygen species (ROS) is 8-oxoG, a highly mutagenic lesion that compromises genetic instability when not efficiently repaired. 8-oxoG is specifically recognized by the DNA-glycosylase OGG1 that excises the base and initiates the Base Excision Repair pathway (BER). Furthermore, OGG1 has not only a major role in DNA repair but it is also involved in transcriptional regulation. Cancer cells are particularly exposed to ROS, thus challenging their capacity to process oxidative DNA damage has been proposed as a promising therapeutic strategy for cancer treatment. Two competitive inhibitors of OGG1 (OGG1i) have been identified, TH5487 and SU0268, which bind to the OGG1 catalytic pocket preventing its fixation to the DNA. Early studies with these inhibitors show an enhanced cellular sensitivity to cytotoxic drugs and a reduction in the inflammatory response. Our study uncovers two unreported off-targets effects of these OGG1i that are independent of OGG1. In vitro and in cellulo approaches have unveiled that OGG1i TH5487 and SU0268, despite an unrelated molecular structure, are able to inhibit some members of the ABC family transporters, in particular ABC B1 (MDR1) and ABC G2 (BCRP). The inhibition of these efflux pumps by OGG1 inhibitors results in a higher intra-cellular accumulation of various fluorescent probes and drugs, and largely contributes to the enhanced cytotoxicity observed when the inhibitors are combined with cytotoxic agents. Furthermore, we found that SU0268 has an OGG1-independent anti-mitotic activity - by interfering with metaphase completion – resulting in a high cellular toxicity. These two off-target activities are observed at concentrations of OGG1i that are normally used for in vivo studies. It is thus critical to consider these previously unreported non-specific effects when interpreting studies using TH5487 and SU0268 in the context of OGG1 inhibition. Additionally, our work highlights the persistent need for new specific inhibitors of the enzymatic activity of OGG1.